Karakteristik dan Kebutuhan Parkir Pada Taman Kopassus Banten: Characteristics and Parking Requirements In Kopassus Park Banten - Suzanti, Wiwien; Asmuni, Asmuni; Panulisan, Bambang Setyo; Nugroho, Yulianto Agung (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The research was conducted at Kopassus Park with the aim of determining Parking Characteristics, including Parking Accumulation, Vehicle Parking Volume, Parking Index, Turn Over, Parking Headway, and Parking Space Requirements. The survey was conducted for a duration of seven days. The data obtained consisted of vehicle entry and exit data for both cars and motorcycles. The research results showed that the maximum parking index for cars on June 18, 2023, was 56%, indicating that the demand for car parking space did not exceed the available parking capacity. Similarly, for motorcycles, the maximum parking index on June 23, 2023, was 28.3%, indicating that the demand for motorcycle parking space did not exceed the available capacity. The minimum headway for cars occurred on June 18, 2023, between 2:00 PM and 3:00 PM, with a value of 3 minutes per vehicle, while the minimum headway for motorcycles occurred on June 18, 2023, between 12:00 PM and 1:00 PM, with a value of 3.75 minutes per vehicle. The largest parking space requirement for cars on June 18, 2023, was 161 square meters, with the parking area for cars at Kopassus Park totaling 569.49 square meters, still able to accommodate vehicles during peak hours. The maximum parking space requirement for motorcycles on June 19, 2023, was 34.5 square meters, with the parking area for motorcycles at Kopassus Park totaling 121.20 square meters.